Electromagnetic energy harvesting—global information database. Issue 1 (30th November 2013) - Guenda, Ludimar; Santana, Emanuel; Collado, Ana; Niotaki, Kyriaki; Carvalho, Nuno Borges; Georgiadis, Apostolos; Dohler, Mischa; Ratti, Carlo; Muñoz, Luis; Chatzimisios, Periklis
ABSTRACT Electromagnetic energy harvesting is one of the most promising technologies for the future of autonomous electronic gadgets and also for making possible the globalisation of the Internet of things concept and consequently smart cities. In order to obtain an optimum dimensioning of the energy requirements in environments where a large quantity of sensors and devices are spread, it is necessary to have a priori knowledge of the amount of energy that is available from existing electromagnetic sources in the surrounding environment. This article presents a geo‐referenced database that can be used to gather information about electromagnetic energy availability around the world. The paper describes the information system architecture that is behind the database structure and the two methods that can be used to gather the electromagnetic information: one based on typical radiofrequency instrumentation and the other one based on the use of smart phones. Copyright © 2013 John Wiley & Sons, Ltd.